The Crosstalk with CXCL10‐Rich Tumor‐Associated Mast Cells Fuels Pancreatic Cancer Progression and Immune Escape - Hanlin Yin; Qiangda Chen; Shanshan Gao; Sami Shoucair; Yuqi Xie; Joseph R. Habib; Taochen He; Wei Gan; Juan Wang; Lei Zhang; Huaxiang Xu; Chenye Shi; et al. (Advanced Science)
Abstract Pancreatic ductal adenocarcinoma (PDAC) is a devastating disease, necessitating approaches to improve prognosis. As the mediator of allergic process, mast cells have been found in various cancers and are associated with survival. However, the biological behaviors of tumor‐associated mast cells (TAMCs) remain unclear. Herein, an excessive infiltration of TAMCs in PDAC is demonstrated, which apparently associated with poor survival in PDAC patients. PDAC cells are found to recruit CXCR2+ MCs into TME, and then inhibited MCs ferroptosis, and maintained their proliferation. Concomitantly, the tumor‐derived exosome miR‐188‐5p activated the PTEN/AKT/GSK3β signaling, further stabilized transcriptional factor ERG by inhibiting its ubiquitin degradation, and finally enhanced the transcription of cxcl10 within TAMCs. In reverse, TAMCs‐derived CXCL10 reversely promoted tumor epithelial‐mesenchymal transition and induced immunosuppressive tumor microenvironment by recruiting CXCR3+ Tregs. Sodium cromoglycate (SCG) is a membrane stabilizer for MCs and confirmed as an effective and widely used agent to block TAMCs‐derived CXCL10 and further sensitize the therapeutic efficacy of anti‐PD‐1 antibody plus gemcitabine for PDAC. These findings illuminate a critical and innovative crosstalk between TAMCs and PDAC cells that promote PDAC progression, and SCG sensitizes PDAC to the current immuno‐chemotherapy, which reveals its potential to be a valuable adjuvant for PDAC patients.